Analysis of growth And Plantbaby Kai-Lan(Brassicaalboglabra L.)The Use of Various Doses of Fertilizer Urea - Bambang Wicaksono Hariyadi; Nurul Huda; Nurlina (Agricultural Science, 2019)
One important factor in cultivation that supports the success of plant life is the problem of fertilization. A common problem that occurs in fertilization is the low efficiency of nutrient uptake by plants. The efficiency of fertilizing nitrogen (N) and potassium (K) is relatively low, ranging from 30-40%. The efficiency of phosphorus (P) fertilization by plants is also low, around 15-20% (Rukmana, 2002). Efforts to improve the efficiency of fertilizer use can be pursued through the principle of the right type, the right dose, the right way, the right time of application and balanced according to the needs of plants (Syafruddin et al, 2009). The purpose of this study was to determine the extent to which the effectiveness (appropriate) use of urea fertilizer (nitrogen sources) on plant growth and yield Baby Kailan (Brassica alboglabra L.). The study was conducted in the Experimental Garden of the Faculty of Agriculture, Merdeka University Surabaya, on Jalan Ketintang Madya VII-2 Surabaya, East Java with a height of ± 5 m above sea level, carried out from March to April 2019. This study used a Randomized Group Design (RBD) consisting six (6) treatments with three (3) replications and two (2) sample plants. As for the treatment given, namely the dose of urea fertilizer consisting of six (6) doses, namely: A = No Urea Fertilizer (Control); B = 75 kg / ha Urea Fertilizer (0.15 gram per plant); C = Urea fertilizer 150 kg / ha (0.30 gram per plant); D = Urea Fertilizer 225 kg / Ha (0.45 gram per plant); E = Urea fertilizer 300 kg / ha (0.60 gram per plant); F = Urea Fertilizer 375 kg / Ha (0.75 gram per plant) The results of the study show that the use of urea fertilizer has a very significant effect on the variable plant length, number of leaves and the wet weight of baby kailan plants. Effective (appropriate) dosage in the use of urea fertilizer during growth and yield of baby kailan plants tends to be achieved with urea fertilizer dosages of 300 kg per hectare (0.60 gram per plant), although the highest growth and yield tends to be indicated by urea fertilizer dosages 375 kg per hectares (0.75 grams per plant), because statistically (LSD 5%) between the two treatments the dose of urea fertilizer was not significantly different.